2023
DOI: 10.1007/s11858-022-01463-2
|View full text |Cite
|
Sign up to set email alerts
|

Emotions and motivation in mathematics education: Where we are today and where we need to go

Abstract: Emotions and motivation are important for learning and achievement in mathematics. In this paper, we present an overview of research on students’ emotions and motivation in mathematics. First, we briefly review how early research has developed into the current state-of-the-art and outline the following key characteristics of emotions and motivation: objects, valence, temporal stability (vs. variability), and situational specificity (vs. generality). Second, we summarize major theories in the field (the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 122 publications
0
12
0
2
Order By: Relevance
“…Support for this is furthermore provided by Stevens et al (2004). They found in ninth- and 10th-grade students that self-efficacy predicted their motivational orientation and subsequently their mathematics performance.…”
Section: Theoretical Perspective and Research Questionsmentioning
confidence: 86%
See 1 more Smart Citation
“…Support for this is furthermore provided by Stevens et al (2004). They found in ninth- and 10th-grade students that self-efficacy predicted their motivational orientation and subsequently their mathematics performance.…”
Section: Theoretical Perspective and Research Questionsmentioning
confidence: 86%
“…The approach of taking into account the situational influences can also be found in the work of Schukajlow et al (2023), who recognized that there is recently increased attention on the situational nature of affective constructs. Therefore, they decided to include in their survey paper, "situational specificity" as a key characteristic of emotions and motivation which can be embedded in social environments and sociocultural contexts as well as in tasks.…”
Section: Crucial Role Of Motivationmentioning
confidence: 99%
“…Furthermore, studies have shown that Chinese students perform well intellectually but poorly emotionally in mathematics (Dowker et al., 2019; Mullis et al., 2020). Despite substantial research on students' academic emotions, research on such emotions in non‐Western classrooms (e.g., China) is inadequate (see Schukajlow et al., 2023). Inspired by the CVT, culture might influence academic emotions via academic control–value appraisals.…”
Section: Academic Emotions and Control–value Appraisalsmentioning
confidence: 99%
“…In the long run, these motivational beliefs importantly shape students’ choices of educational and career‐related pathways (Simpkins et al., 2006; Viljaranta, Nurmi, et al., 2009; Watt, 2006; Watt et al., 2012). The expectancy–value framework has been extensively applied in studies linking mathematics motivation with both achievement and mathematics‐related educational and occupational choices (Aunola et al., 2006; Lauermann et al., 2017; Lazarides et al., 2018; Watt et al., 2012), thus making it highly relevant for mathematics education (Schukajlow et al., 2017).…”
Section: Introductionmentioning
confidence: 99%